2020
DOI: 10.1111/jocs.14494
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of aortic arch reconstruction with branch pulmonary artery homograft patches

Abstract: Background Homograft tissue is an important reconstructive material used in the surgical correction of a variety of congenital heart defects. The aim of this study is to evaluate the long‐term outcome of pulmonary artery (PA) branch patches used in the reconstruction of the thoracic aorta in children. Methods Retrospective review of 124 consecutive pediatric patients undergoing corrective surgery for their congenital heart defects between 2001 and 2016. Survival, reoperation, and reintervention data were colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…1 The advancement in clinical practice and the use of moderate to deep hypothermic circulatory arrest combined with adjunct brain protection in the form of selective cerebral perfusion have had significant impact on improved outcomes over the period of time. 4,5 There is wide variation in practice and reported outcomes, especially early and late mortality. 4,5,6,7 Rakhra et al reported their outcomes on 305 patients that had AAH and coarctation repair with an early mortality rate of 9% and re-intervention rate was needed on eight patients prior to discharge from the hospital due to residual obstruction while late re-interventions of 66 accounts were reported in 49 (18%) patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The advancement in clinical practice and the use of moderate to deep hypothermic circulatory arrest combined with adjunct brain protection in the form of selective cerebral perfusion have had significant impact on improved outcomes over the period of time. 4,5 There is wide variation in practice and reported outcomes, especially early and late mortality. 4,5,6,7 Rakhra et al reported their outcomes on 305 patients that had AAH and coarctation repair with an early mortality rate of 9% and re-intervention rate was needed on eight patients prior to discharge from the hospital due to residual obstruction while late re-interventions of 66 accounts were reported in 49 (18%) patients.…”
Section: Discussionmentioning
confidence: 99%
“…3 Nowadays, AAH reconstruction using pulmonary homograft patch with coarctation excision is the preferred technique for repair. 4,5 This procedure is performed on cardiopulmonary bypass (CPB) under deep hypothermic circulatory arrest with retrograde cerebral perfusion (RCP). 4,5 Recurrent aortic arch obstruction and neurological adverse events are common complications following AAH reconstruction.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The authors considered the allograft patches harvested from PA branches to be an effective material for reconstruction of the aorta in small children. Long-term results showed no risk of aneurysm formation and low rates of stenosis formation (Lewis 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…For the reconstruction of the aortic arch in newborn patients and children, our institution distributed 643 allografts or approximately 15% of all distributed CVAs (during the second and third periods) and approximately 10% during the first period. Many paediatric cardiac surgeons consider the cryopreserved allogenic nonvalvular pulmonary conduit (nVPC) as a “gold standard” for the repair of hypoplastic left heart syndrome (HLHS) or arch interruption (Amri 2022 ; Lewis 2020 ; van Beynum 2021 ). Our TE distributed 46, 220 and 377 nVPCs during the first, second and third periods, respectively, presenting an increase of 478% in the second and 171% in the third period compared to the previous period.…”
Section: Discussionmentioning
confidence: 99%